The Correlation of Student Engagement using Kahoot on Learning Outcomes in Junior High School - Nadima, Ismi Syifa; Halim, Abdul (Juwara: Jurnal Wawasan dan Aksara, 2024)
This study aims to explore the relationship between the use of Kahoot and student engagement in learning at SMP Negeri 22 Samarinda, focusing on addressing the issue of low student engagement and how Kahoot can potentially enhance it. A correlational quantitative research design was employed, with a randomly selected sample of students from class VII B. Data were collected through both observations and surveys. The findings revealed a significant positive correlation between the use of Kahoot and student engagement, indicating that Kahoot's interactive and gamified features effectively increased student participation and focus in the learning process. Additionally, the study found that this enhanced engagement positively impacted students' learning outcomes. The results suggest that the integration of Kahoot as an educational tool can improve student motivation, interactivity, and overall satisfaction, making it an effective method for increasing engagement and boosting academic achievement. These findings are expected to provide valuable insights for educators seeking to enhance student engagement and learning outcomes through the use of technology.